2020
DOI: 10.21147/j.issn.1000-9604.2020.04.10
|View full text |Cite
|
Sign up to set email alerts
|

Virtual bronchoscopic navigation without fluoroscopy guidance for peripheral pulmonary lesions in inexperienced pulmonologist

Abstract: Objective Fluoroscopy guidance is generally required for endobronchial ultrasonography with guide sheath (EBUS-GS) in peripheral pulmonary lesions (PPLs). Virtual bronchoscopic navigation (VBN) can guide the bronchoscope by creating virtual images of the bronchial route to the lesion. The diagnostic yield and safety profiles of VBN without fluoroscopy for PPLs have not been evaluated in inexperienced pulmonologist performing EBUS-GS. Methods Between January 2016 and Jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…In subgroup analysis with PPLs ≤30 mm, the results were also confirmed. These results were comparable or superior to those from previous studies of VBN‐rEBUS‐GS without fluoroscopy 14–16 . This could be related to the present study including substantial proportions of relatively large lesions (>30 mm, 53.3%), within two‐third from hilum (66.9%) and malignant lesions (80.8%) 6,7,24 .…”
Section: Discussionsupporting
confidence: 87%
“…In subgroup analysis with PPLs ≤30 mm, the results were also confirmed. These results were comparable or superior to those from previous studies of VBN‐rEBUS‐GS without fluoroscopy 14–16 . This could be related to the present study including substantial proportions of relatively large lesions (>30 mm, 53.3%), within two‐third from hilum (66.9%) and malignant lesions (80.8%) 6,7,24 .…”
Section: Discussionsupporting
confidence: 87%
“…Yoshikawa et al have reported that EBUS‐GS‐guided bronchoscopy without fluoroscopy is an effective method for diagnosing PPLs using conventional videobronchoscopy 11 . In addition, recent reports have shown that use of a 4.0‐mm outer diameter thin bronchoscope combined with VBN and EBUS‐GS is a feasible option for the diagnosis of PPLs 12,13 . Another preliminary randomized controlled trial evaluated the diagnostic value of VBN‐EBUS‐GS with or without X‐ray fluoroscopy in 31 patients with PPLs of ≤30 mm, with comparable diagnostic yields between the X‐ray and non‐X‐ray groups, especially for malignant lesions 14…”
Section: Introductionmentioning
confidence: 99%
“…VBN is regarded as a relatively more economical and less harmful guidance method and is even equally effective with fluoroscopic guidance in diagnosing PPNs. 10 , 11 However, in a few cases, the nodule could not be visualized by rEBUS, even if those techniques were used in combination. If transbronchial biopsy is performed on these rEBUS-invisible nodules, it will present a particular problem that it becomes a “blind” biopsy.…”
Section: Discussionmentioning
confidence: 99%